2023
DOI: 10.1038/s43705-022-00211-7
|View full text |Cite
|
Sign up to set email alerts
|

DNA uptake from a laboratory environment drives unexpected adaptation of a thermophile to a minor medium component

Abstract: DNA uptake is widespread among microorganisms and considered a strategy for rapid adaptation to new conditions. While both DNA uptake and adaptation are referred to in the context of natural environments, they are often studied in laboratories under defined conditions. For example, a strain of the thermophile Thermoanaerobacter kivui had been adapted to growth on high concentrations of carbon monoxide (CO). Unusual phenotypes of the CO-adapted strain prompted us to examine it more closely, revealing a horizont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Two more are located in transcriptional regulators that have relatively low expression levels at 66°C (unpublished data), but may be of importance in cold adaptation. Since T. kivui easily takes up and integrates environmental DNA at 66°C (Basen et al, 2018 ; Zeldes et al, 2023 ), the SNP in Cas6-1, a CRISPR RNA maturation endonuclease (Jesser et al, 2019 ), may modulate the ability to acquire foreign DNA as a strategy for the adaptation of the environment. Another SNP was detected in the gene encoding the potassium ATPase kdpC N146K (AAT → AAG).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two more are located in transcriptional regulators that have relatively low expression levels at 66°C (unpublished data), but may be of importance in cold adaptation. Since T. kivui easily takes up and integrates environmental DNA at 66°C (Basen et al, 2018 ; Zeldes et al, 2023 ), the SNP in Cas6-1, a CRISPR RNA maturation endonuclease (Jesser et al, 2019 ), may modulate the ability to acquire foreign DNA as a strategy for the adaptation of the environment. Another SNP was detected in the gene encoding the potassium ATPase kdpC N146K (AAT → AAG).…”
Section: Resultsmentioning
confidence: 99%
“…On a shorter time scale, it may be conceivable that thermophiles profit from HGT events in adaptation to lower temperatures. T. kivui , the organism used in this study, has recently been shown to efficiently take up and integrate foreign DNA from a laboratory environment into its genome, which allowed the strain to adapt to a certain medium type (Zeldes et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain differences between the topologies of particular trees are likely to result from subsequent gene replacements via HGT across shorter phylogenetic distances. The members of the TTC group seem prone to ready acquisition of genetic information, as evidenced by demonstration of wide occurrence of natural competence among Thermoanaerobacter and Thermoanaerobacterium species (Shaw et al, 2010;Zeldes et al, 2023).…”
Section: On the Likely Evolutionary Origin Of Acetogenic Metabolism I...mentioning
confidence: 99%